The Development of Backend Admin Dashboard for Business Project Monitoring using Scrum method: A case study at PT Gerbang Sinergi Utama - Eko Darwiyanto; Rio Nurtantyana; Hutomo Putra, Daffa Arya (Indonesia Journal on Computing (Indo-JC), 2024)
Monitoring business projects is very important to ensure project performance goes according to plan. PT Gerbang Sinergi Prima (GSP) is one of the subsidiaries of the Pension Fund of PT PLN (Persero), which is engaged in Information and Communication Technology. Currently, GSP monitors project performance in a conventional way, which creates several challenges, such as difficulties in monitoring project progress and development. This study aims to develop a backend as an admin dashboard for a business project monitoring system using the Scrum method. Unlike other studies, this research also tests the results obtained with three tests, namely Black-Box Testing, Unit Testing, and Performance Testing. As a result, we built a backend admin dashboard for business project monitoring that supports GSP in real-time monitoring the progress of business projects. Furthermore, testing will also be conducted on the backend admin dashboard. The Scrum method was implemented with excellent results. Feature functionality testing using black-box testing gets a percentage of 100%. API testing using unit testing receives a percentage of 100%. The average response time obtained after executing performance testing is 2896.72ms, which means the results are feasible. Overall, the process of development and testing received excellent results.